Rugged Resonances: From Music in McCarthy to McCarthian Music - Julius Greve; Markus Wierschem (European Journal of American Studies)
This essay explores the contact zone between the two worlds of music and literature, or sound and fiction, in the context of Cormac McCarthy’s works. It teases out the stylistic idiosyncrasies of McCarthy’s fiction in terms of a sonic register, by tracing its connections to the film scores of movie adaptations like All the Pretty Horses (2000) and The Road (2009), and to the works of a diverse set of musicians and bands directly inspired by McCarthy’s fiction, including acts like Buddy and the Huddle, Horatio Clam, Ben Nichols, Earth, and Neurosis. Starting with specific passages from the author’s oeuvre that themselves project a sonic imagery, the guiding question of this essay will be in what sense a tracing of the film scores and musical acts inspired by McCarthy’s writings shed light on the “ruggedness” of what could be called his “signature resonance.”